Portrait of Parenting for Extended Family Through the Tradition of "Turun Mandi" in Minangkabau - Gustiani, Rima; Listiana, Aan (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
Tradition is a valuable treasure in every culture that should be preserved and maintained. One tradition still being applied in Minangkabau is turun mandi.  Minangkabau is known for its ethnicity that uses the mother's lineage; this system allows children to be born and grow up in their mother's family and will have less time with their father's family. For this reason, the tradition in Minangkabau called turun mandi regulates the involvement of the father's family in parenting. This article aims to describe the father's family's involvement in the extended family's care through this tradition. This study uses a literature study approach that uses various related articles as data sources, and this study also uses content analysis and descriptive analysis in analyzing data. The results of the research are divided into three parts; Portraits of extended families in parenting in Indonesia, family gratitude for the birth of a child, involvement of an extended family since the birth of a child in Minangkabau, a gift from the father's family (bako) as a guide for the child.